Pengaruh Media Articulate Storyline 3 Terhadap Hasil Belajar Kognitif Matematika Siswa Kelas V - Anggraeni, Listiana; Manan, Nanan Abdul (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This study aims to find out whether there is an effect of the use of articulate storyline 3 media on the cognitive learning outcomes of grade V students of SDN 2 Ciherang. The research approach used is a quantitative approach with a quasi experiment design type of research design. The population in this study is 44 students with a sample of class V of SDN 1 Ciherang consisting of 22 students as the control class and class V of SDN 2 Ciherang consisting of 22 students as an experimental class. Data on students' cognitive learning outcomes were obtained from the results of the description test. After the application of the media, there were before and after results, which showed that the pretest results in the experimental class had a mean of 41.45 and in the control class had a mean of 38.18. The results of the posttest in the experimental class had an average value (mean) of 83.36 and in the control class had an average value (mean) of 67.82. Media articulate storyline 3 has an influence on students' cognitive learning outcomes in mathematics. This is shown from the results of data analysis that the Asymp Sig. (2-tailed) value is 0.000 < 0.05, where if the Asymp Sig. (2-tailed) value > 0.05, H0 is accepted, while if the Asymp Sig. (2-tailed) value < 0.05, H0 is rejected. Therefore, because the significance value is 0.000 < 0.05, H0 is rejected and H1 is accepted, so there is an influence of media articulate storyline 3 on the cognitive learning outcomes of mathematics in the experimental class compared to the control class.